Effect of Potassium Permanganate and Zeolite on Shelf Life and Quality of Musa Acuminata - Chong Yi Yin (School of Bioprocess Engineering, University Malaysia Perlis, 2019)
To evaluate the physico-chemical changes of M.acuminata during ripening throughout the storage period. To evaluate the effectiveness of ethylene scavenger (KMnO4 -Zeolite) in different dosage quantity towards the shelf life and quality of M. acuminata. To analyze the effect of perforated and non-perforated packaging on shelf life and quality of M. acuminata.